(untitled) (Journal of Teleological Science, 2022)
Gender ideology emerges as the next phase of the more mature relativism that in turn found its roots in post-Marxism and structuralism from Gilles Deleuze to Michel Foucault, but which had already recovered wide openness in the analytical philosophy of Jules Viullemin and in the Marxian existentialism of Jean-Paul Sartre. The cult of the body as absolute self and the search for an overlapping of culture on nature, of civilization on civilization, outline in genderism a propensity for colonization of the human person, led to confuse the protection of individual rights and the protection of fundamental freedoms as a particular guarantee of an even axiological choice which, from being an ideological expression of a sexual orientation, leads solely to the categorized, destructive omesessualization of God’s creative plan precisely because it stands to be and become not a personal choice, but politically and ideologically personalizing, so as to change the sense of reality and creation, of words and things to the point of proposing collectivization, highlighting in this hysterical and obsessive characters, especially when a pedagogical use is proposed or no less if they are identified as characters of university training and research courses.